PROTEIN CONTENT IN NEOMETADIDYMOZOON POLYMORPHIS (TREMATODA : DIDYMOZOIDAE) AND IN INFECTED, UNINFECTED GILL TISSUE OF THE HOST PRIACANTHUS HAMRUR - KRISHNA, P. V.; MULU, KOLLURI SREERA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1996)
Marine fish Priacanthus hamrur collected from the Waltair coast, examined for the didymozoid parasites. Biochemical studies show total protein content in parasite (Neometadidymozoon polymorphis) 5.5 mg/100 mg dry tissue, uninfected gill tissue 22.5mg/100 G. y tissue, infected 6.5 mg/100 mg dry tissue.